Association of vitamin D receptor gene variants with polycystic ovary syndrome: A case control study - Touraj Mahmoudi; Keivan Majidzadeh-A; Hamid Farahani; Mojgan Mirakhorli; Reza Dabiri; Hossein Nobakht; Asadollah Asadi (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: Vitamin D and insulin play an important role in susceptibility to polycystic ovary syndrome (PCOS), and therefore vitamin D receptor (VDR), parathyroid hormone (PTH), and insulin receptor (INSR) gene variants might be involved in the pathogenesis of PCOS. Objective: The present study was designed to investigate the possible associations between polymorphisms in VDR, PTH, and INSR genes and the risk of PCOS. Materials and Methods: VDR, PTH, and INSR gene variants were genotyped in 35 women with PCOS and 35 controls using Polymerase chain reaction - Restriction fragment length polymorphism method. Furthermore, serum levels of glucose and insulin were measured in all participants. Results: No significant differences were observed for the VDR FokI, VDR Tru9I, VDR TaqI, PTH DraII, INSR NsiI, and INSR PmlI gene polymorphisms between the women with PCOS and controls. However, after adjustment for confounding factors, the VDR BsmI "Bb" genotype and the VDR ApaI "Aa" genotype were significantly under transmitted to the patients (p= 0.016; OR= 0.250; 95% CI= 0.081-0.769, and p= 0.017; OR= 0.260; 95% CI= 0.086-0.788, respectively). Furthermore, in the women with PCOS, insulin levels were lower in the participants with the INSR NsiI "NN" genotype compared with those with the "Nn + nn" genotypes (P= 0.045). Conclusion: The results showed an association between the VDR gene BsmI and ApaI polymorphisms and PCOS risk. These data also indicated that the INSR "NN" genotype was a marker of decreased insulin in women with PCOS. Our findings, however, do not lend support to the hypothesis that PTH gene DraII variant plays a role in susceptibility to PCOS.